Editorial for the Special Issue on “Crystalline Materials for Radiation Detection: A New Perspective” - Ivana Capan; José Coutinho; Vladimir Radulović; Takahiro Makino (Crystals, 2021)
The development of efficient and environmentally friendly technologies for radiation detection is a great challenge [...]